ANALISIS PAJAK TANGGUHAN PADA PT PERUSAHAAN PERKEBUNAN LONDON SUMATRA INDONESIA TBK - Tangdialla, Luther P.; Pasanda, Erna (Jurnal Riset Akuntansi (JUARA), 2019)
Deferred tax is one of the interesting topics to be studied in every financial accounting literature. This deferred tax arises as a result of temporary between commercial financial statements and fiscal financial statements. If this temporary difference reduces commercial profit, it will result in deferred tax expenses and deferred tax liabilities, and if the reversed condition happened, it will be result in deferred tax benefit and deferred tax assets The aim of this research is to find out of the application of PSAK No. 46 concerning income tax accounting, calculation and presentation in the financial statements . The result shows that the impact of the temporary difference between commercial financial statements and fiscal financial statements is the arising of deferred tax expenses of Rp 3,281,000,000 in 2017 and the benefits of deferred tax of Rp 18,966,000,000 in 2016